Generational Cohort and Psychographic Effects for Market Segmentation in Malaysia - Lim, Tze Yin (2020)
This study aims to propose the generational cohorts and generational psychographic effects for market segmentation in the context of Malaysia. In spite of the widely cited generational cohort labels in marketing as one of the innovative segmentation strategies, arguments and doubts arise pertaining to the use of this approach in terms of theoretical foundation and empirical evidences. This study investigates the external life events recalled by individuals during their formative years. Generational values and lifestyles for each of the proposed generational cohort in Malaysia are explored for the purpose of market segmentation in marketing. Furthermore, generational cohort theory and market segmentation theory are employed as theoretical grounding in the current study. The current study utilized qualitative approaches in order to understand the experiences shared among individuals and at the same time, proposed an explanatory model which highlight the formation of generational cohorts and the psychographic effects in Malaysia. Content analysis, document analysis and grounded theory procedure were implemented in data analysis to highlight the deeper insights provided by the participants in the country. Additionally, interviews were conducted throughout the whole nation with interview guidelines prepared and applied during the interview sessions. This study utilized semi-structured interview with proper probing questions in order to gain insights shared by the individuals. Participants comprised of Malaysians age 15 and above and who are currently residing in the country. There are 80 transcripts that have been reviewed during the data collection and data analysis procedure throughout the study. Malaysia as an important emerging market and developing country is chosen as the context for this study due to the country’s distinctive characteristics and dynamics from the perspective of historical, economic and societal background. The qualitative findings suggest five Malaysia generational cohorts, namely The Discoverers, The Innovators, The Believers, The Strivers and The Survivors. Each of them demonstrates diverse external and internal characteristics due to the impacts of external life events during their formative years. Moreover, psychographic effects such as generational values and generational lifestyles are shown in each cohort as the outcomes of the impactful external life events. The qualitative findings of the current study contribute theoretically by extending the generational cohort theory and market segmentation theory, especially by proposing generational cohort and psychographic effects as a hybrid approach for market segmentation in Malaysia. In addition, the external and internal characteristics for each generational cohort are discovered. At the same time, the homogeneous and heterogeneous characteristics across cohorts in the country are also demonstrated. In terms of managerial perspective, the current study enables marketers and firms to identify the actual generational cohorts with their respective generational characteristics in the Malaysian context.